Technical and economic feasibility of ceramic waste as a coarse concrete aggregate (2018)
The production of solid waste continues to increment over the world. In Colombia waste generation grew 13% in only 6 years. This has led to a sanitary landfill crisis in various municipalities, like Medellín, where its main landfill La Pradera has only 7 years of lifespan and no current backup plan. This has created a massive necessity for alternative ways to waste reutilization and development into a circular economy. One of the industries present in the Valle de Aburrá is GAMMA, a ceramic insulator producer, for which approximately 10% of the monthly production is waste. Ceramic waste can be very harmful to the environment causing high concentration of Magnesium or Iron in the soil, also its degradation can take thousands of years. The infrastructure sector is one of the main factors in the economy, where concrete is a raw material with a great potential for residue reutilization. Eco-efficient concretes made from ceramic waste have been studied and shown to be compliant regarding compressive resistance demanded by standards (BS EN 12390-6:2001) [1]. In this study, ceramic electrical insulators are used as a coarse aggregate in concrete manufacturing for different substitution percentages of coarse aggregate (0%, 25%, 50%, 75% and 100%). Our results confirm the performance potential and the economic viability of the material for the proposed scenarios when compared to conventional concrete. The 25% of coarse aggregate replacement was the only mixture compliant with Colombian standards having an average compressive resistance of 28.05 MPa after 28-day of setting. For both the modified and conventional concrete, the workability results were 7cm within the required range of 2,5 and 7,5cm for structural concrete.